Conservation agriculture-based crop diversification options provide sustainable food and nutritional security in the Eastern Gangetic Plains of India - Bijarniya, Deepak; Gathala, Mahesh Kumar; Kalvania, Kailash C.; Jat, R. K.; Singh, Yadvinder (Frontiers in Agronomy, 2025)
The conventional rice-wheat system in eastern India faces serious challenges, including declining productivity, inefficient use of water and energy resources, and degradation of soil health. Despite being central to regional food security, the system’s sustainability is increasingly under pressure. The hypothesize will boost productivity, conserve water, increase profits, and improve nutrition for resource-poor farmers. An on-farm study was conducted over three cropping cycles (2016-2019) in three villages in two districts (Vaishali and Samastipur) of Bihar. Five diversified cropping systems were tested under different establishment practices viz., conventionally established rice and wheat (CT-RW), conservation agriculture-based rice-wheat (CA-RW), conventional rice with conservation agriculture mustard and mungbean (partial CA-RMuMb), conservation agriculture maize and wheat (CA-MW), and conservation agriculture maize, mustard and mung bean (CA-MMuMb) systems. Systems productivity, irrigation water, energy use efficiency, and nutritional yields (protein, fat, iron, zinc) were assessed. The CA–MMuMb system achieved 52.6% higher system productivity (15.01 t ha-¹) and 63.2% higher net income (USD 2,046 ha-¹) compared to the CT–RW system (9.83 t ha-¹ and USD 1,253 ha-¹, respectively). The irrigation water productivity and energy productivity recorded 4.0 and 2.4 times higher (6.06 kg grain M-3 ha-¹) water and 0.68 kg grain MJ-1) compared to CT-RW system (1.5 kg grain M-3 ha-¹) and 0.28 kg grain MJ-1 respectively). Furthermore, this diversified cropping system resulted in 30.9, 1125, 119 and 26.5% higher protein, fat, iron and zinc yields, respectively, compared to the baseline CT-RW system. The CA-MW system achieved similar benefits in productivity and nutritional yields. These emerging systems can enhance sustainable food production and nutritional security. The CA-MMuMb system is a scalable approach to enhance productivity, save natural resources (water and energy), and improve nutritional yields in eastern India, with implications for similar irrigated ecologies across South Asia.